The Role of T Cell Receptor Signaling in the Development of Type 1 Diabetes - Clark, Matthew; Kroger, Charles J.; Ke, Qi; Tisch, Roland M. (Frontiers in Immunology, 2021)
T cell receptor (TCR) signaling influences multiple aspects of CD4+ and CD8+ T cell immunobiology including thymic development, peripheral homeostasis, effector subset differentiation/function, and memory formation. Additional T cell signaling cues triggered by co-stimulatory molecules and cytokines also affect TCR signaling duration, as well as accessory pathways that further shape a T cell response. Type 1 diabetes (T1D) is a T cell driven autoimmune disease targeting the insulin producing β cells in the pancreas. Evidence indicates that dysregulated TCR signaling events in T1D impact the efficacy of central and peripheral tolerance-inducing mechanisms. In this review, we will discuss how the strength and nature of TCR signaling events influence the development of self-reactive T cells and drive the progression of T1D through effects on T cell gene expression, lineage commitment, and maintenance of pathogenic anti-self T cell effector function.